LIDT-DD: A New Self-Consistent Debris Disc Model Including Radiation Pressure and Coupling Dynamical and Collisional Evolution. Issue Volume 8:Issue S299(2013) (6th January 2014) - Kral, Q.; Thebault, P.; Charnoz, S.
Abstract: The first attempt at developing a fully self-consistent code coupling dynamics and collisions to study debris discs (Kral et al . 2013) is presented. So far, these two crucial mechanisms were studied separately, with N-body and statistical collisional codes respectively, because of stringent computational constraints. We present a new model named LIDT-DD which is able to follow over long timescales the coupled evolution of dynamics (including radiation forces) and collisions in a self-consistent way.